Calcium imaging tension recordings and pelet transit in mouse colon in response to direct electrical field stimulation - Heredia, Dante; Gould, Thomas (SPARC Portal, 2024)
Effect of electrical field stimulation (EFS) of the proximal or distal mouse colon on colonic contractions, colonic pellet transit, and colonic neuron/ICC calcium activity
Comprehensive Structural and Functional Mapping of Mammalian Colonic Nervous System